A review on global perspectives of sustainable development in bioenergy generation. (March 2022) - Duarah, Prangan; Haldar, Dibyajyoti; Patel, Anil Kumar; Dong, Cheng-Di; Singhania, Reeta Rani; Purkait, Mihir Kumar
Graphical abstract: Highlights: Present status on generation of different forms of bioenergy. Bioenergy policy initiatives undertaken by various federal agencies of countries. Feedstock utilization, blending targets, and policy assistance schemes assessed. Current bioenergy market scenario analysis. Abstract: Over the last few decades, the globe has much relied on fossil fuels; however, environmental concerns forced the World to look at biofuel as an alternative for stable economic development. Biofuel also facilitates national energy security maintenance and reduces environmental complications. The present study is focused on an in-depth analysis of bioenergy policy measures undertaken by various federal agencies of different countries in order to shed light on the bottlenecks that impede biofuel's growth as a sustainable and alternative fuel. An in-depth assessment of feedstock utilization, blending targets, and policy assistance schemes have been thoroughly reviewed. In addition, the potential of commercial firms for the production of bioenergy is highlighted in order to grasp the current bioenergy market scenario better. Finally, the article is concluded with the viewpoints of the authors to address the standing issues of global bioenergy generation.